ESTIMATION OF METRONIDAZOLE, FURAZOLIDONE AND LOPERAMIDE IN VETERINARY FORMULATION BY RP-HPLC - J. KAVITHA,; KRISHNA KISHORE.CH,; K.S.LAKSHMI, (International Journal of Pharma and Bio Sciences, 2014)
A RP-HPLC method for the simultaneous estimation of Metronidazole(MTZ), Furazolidone(FZD) and Loperamide(LOP) was developed which was simple, precise, accurate and sensitive. The chromatographic elution was carried out by using C18 column (150×4.6mm) with optimized mobile phase Acetonitrile: Double distilled water in the ratio of 10:90%v/v detected at a wavelength of 230nm. The Retention time was found to be 5.35, 16.59 and 6.84 for MTZ, FZD and LOP respectively. The method was validated according to ICH guidelines and the reliability of the method was assed by the evaluation of Linearity range from 160-240µg for MTZ and LOP, 60-140µg for FZD, The percentage recovery in Recovery studies was found to be 99.34– 100.90% w/w. The proposed method was simple, accurate, precise and sensitive. This method can be used for the routine analysis of these drugs in pharmaceutical and veterinary formulations.